Analysis of the perception of free shipping promotions on purchasing decisions on the Shopee marketplace - Sentot Basuki Prayitno (Institute of Computer Science (IOCS), 2023)
The free shipping promotion is one of many factors that influence purchasing decisions on the Shopee marketplace. The purpose of this study is to ascertain people's perceptions of the impact of free shipping Shopee promotions on purchasing decisions. A qualitative research approach is used in this study. This study relied on primary data gathered through interviews. The Snowball Sampling method was used to find 11 informants majoring in management at Sampoerna University. The study was carried out between January and February of 2023. In the data analysis process, this study used data reduction, data display, and conclusion. The findings of this study indicate that Shopee's free shipping promotion affects purchasing decisions, with buyers believing that free shipping promotions allow them to save more money, making them more enthusiastic about buying or transacting with the application. Promotions and prices influence purchasing decisions, which are supported by indicators such as advertising, personal selling, sales promotion, publicity, affordability, price per product, and price per benefit, being able to compete with other companies to influence purchasing decisions based on indicators such as product choices, brands, and more